Biologia de Ophiodes fragilis (Squamata: anguidae): dieta e reprodução, no sul do Brasil - Montechiaro, Leandro (2008)
Ophiodes fragilis is a medium sized legless lizard which belongs to the Anguidae family. The species occurs in the southern and southeastern Brazil, southern coast of Bahia, Minas Gerais, Mato Grosso do Sul and northeastern Argentina. In the present work the dissection of 249 specimens of the anguid O. fragilis from the states of Rio Grande do Sul, Santa Catarina and Parana, provided data about diet, reproductive biology and sexual dimorphism for the Brazilian southern region. The O. fragilis diet is composed of arthropods, mollusks and vertebrates. Araneae was the item most frequently found, while Isopoda was quantitatively the most expressive, and Orthoptera was the most significant volumetrically. There wasn’t ontogenetic variation in the diet of the species, although there is a significant difference in the number of preys consumed by males and females. The reproductive cycle in females is seasonal, and in the males it is not seasonal. Vitelogenic folicules and eggs occur from February to October; and embryos, from July to December. The recruitment was registered in December. The SVL among the mature females varied from 107 to 220 mm, and in the mature males varied from 105 to 195 mm. The number of vitelogenic folicules or embryos varied from 2 to 16, and the relation to the female SVL was positive and significant. Mature females showed an SVL significantly longer to mature males, while mature males showed tail length, head length and wide and posterior members significantly higher than mature females.